Faktor-faktor yang Mempengaruhi Kepatuhan Minum Obat pada Penderita Tuberkulosis Paru di RS Bhayangkara TK. II Jayapura - Junitha Sari Tambane; Hernandia Distinarista; Tutik Rahayu (PPNI UNIMMAN, 2025)
Tuberculosis remains a global health problem, and Indonesia, among three countries, accounts for 60% of the world's 809,000 tuberculosis cases. Preventive measures to prevent the transmission of pulmonary TB include adherence to medication to expedite the healing process and prevent the spread of the disease within the families and communities of TB patients. The purpose of this study was to identify factors influencing medication adherence in pulmonary tuberculosis patients at Bhayangkara Hospital Class II, Jayapura. This research was an analytical study with a cross-sectional design. Data were collected using a questionnaire. A total of 88 respondents were selected using a simple accidental sampling technique. The data were statistically analyzed using the chi-square formula. The results of the study showed that factors that did not affect adherence to taking medication in pulmonary TB patients were age (p-value 1,000 > α (0.05), gender (p-value 0.473 > α (0.05), education (p-value 0.525 > α (0.05), occupation (p-value 0.881 > α (0.05). Meanwhile, there was an influence of the duration of treatment as well as being a dominant factor influencing adherence to taking medication in pulmonary TB patients at the Lung Polyclinic of Bhayangkara Hospital Level II Jayapura (p-value 0.001 p < (0.05). The duration of treatment is an obstacle for pulmonary TB patients regarding adherence to taking medication due to saturation, boredom and side effects.